2014
DOI: 10.1039/c4ta03197k
|View full text |Cite
|
Sign up to set email alerts
|

A straightforward, eco-friendly and cost-effective approach towards flame retardant epoxy resins

Abstract: Commercial epoxy resin loaded with phosphorus flame retardant led to composites exhibiting remarkable improved flame retardancy and thermal stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(84 citation statements)
references
References 69 publications
0
84
0
Order By: Relevance
“…It is possible that phosphorus-based acid such as phosphoric acid and polyphosphoric acid, generated from the thermal degradation of DAP and AP moiety in thermosets, can react with the decomposed matrix to promote the formation of char residues. 31,32 It is worth noting that EP/AP10 possesses a higher char yield than EP/DAP10 at elevated temperature in both air and nitrogen, whereas it achieves inferior flame retardancy as mentioned previously. In view of the loose char layer of EP/AP10 presented in Figure 3, it is not difficult to speculate that the quality rather than the amount of residual char plays a pivotal role in enhancing the flame retardancy of epoxy thermoset.…”
Section: Thermal Stabilities Of Dap Ap and Epoxy Thermosetsmentioning
confidence: 87%
“…It is possible that phosphorus-based acid such as phosphoric acid and polyphosphoric acid, generated from the thermal degradation of DAP and AP moiety in thermosets, can react with the decomposed matrix to promote the formation of char residues. 31,32 It is worth noting that EP/AP10 possesses a higher char yield than EP/DAP10 at elevated temperature in both air and nitrogen, whereas it achieves inferior flame retardancy as mentioned previously. In view of the loose char layer of EP/AP10 presented in Figure 3, it is not difficult to speculate that the quality rather than the amount of residual char plays a pivotal role in enhancing the flame retardancy of epoxy thermoset.…”
Section: Thermal Stabilities Of Dap Ap and Epoxy Thermosetsmentioning
confidence: 87%
“…Four bands with binding energy of 530.8, 531.5, 532.2 and 533.2 eV are observed in the O1s spectrum. The peaks at 530.8 and 531.5 eV are attributed to the =O in carbonyl or phosphate[44,45]. The peak at 532.2 eV is assigned to the -O-in P-O-P, C-O-P or C-O-C, and the peak at 533.2 eV is due to the presence of Ph-CO-O-structure.…”
mentioning
confidence: 97%
“…As flame spread on the surface of the materials, a thin continuous carbonaceous layer was generated, which remained intact for a short period of time. After that, the carbonaceous layers were destroyed by the vigorous fuel gas, which formed the second peak [2,24,45]. The P-HRR value was further decreased with the increasing content of HP-1001-COOH.…”
Section: Cone Calorimetric Analysismentioning
confidence: 94%
“…It can introduce more phosphorus element into epoxy resin matrix. Carja et al prepared a new phosphorus flame retardant (13.5 wt.% phosphorus) with a bisphenol-A based epoxy polymer [24]. Thermo-gravimetric data showed that the flame retardant significantly increased the char yield and thermal stability of epoxy resins.…”
Section: Introductionmentioning
confidence: 97%